IMPLEMENTASI KEBIJAKAN PEMBANGUNAN INFRASTRUKTUR JALAN DI KECAMATAN TABIR SELATAN KABUPATEN MERANGIN DENGAN MENGGUNAKAN MODEL DONALD VAN METTER DAN CARL VAN HORN - Wahyu Kurniawan; Karjuni Dt. Maani (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2019)
Policy implementation are actions taken by individuals or groups of government or private sector to achieve the goals specified in previous policy decisions. This study was designed to describe the six variables of the Donald Van Metter and Carl Van Horn models in the implementation of road infrastructure development policies in the South Tabir District of Merangin Regency which connects Gading Jaya village with Muara Delang village. This type of research is a qualitative descriptive study. There are variable models of Donald Van Metter and Carl Van Horn, standard; destination; and policy objectives, resources, characteristics of implementing organizations, implementers' attitudes, communication between organizations, socio-economic and political environments. PT. SAL and PT. Shogun Judging from the six variables in the Donald Van Metter and Carl Van Horn models in the implementation of road infrastructure development in the South Tabir District has been successfully carried out. This can be seen from having been built with number one quality increased 8.2 Km. This construction has been carried out from 2017 to 2019 with the target of road construction as far as 9.3 Km.